Implementation of Bandwidth Management and Access Restrictions Using PCQ and Firewall Methods in SMP Tunas Bangsa Network - Sari, Linna Oktaviana; Utari Nurul Fajar Nasution; Safrianti, Ery; Feranita Jalil (International Journal of Electrical, Energy and Power System Engineering, 2022)
Internet virtual classes as a substitute for face-to-face learning are becoming common use in schools during the pandemic, which activities outside the home is restricted. SMP Tunas Bangsa has an internet hotspot to access Zoom as a virtual class while browsing activities carried out by the teachers. Diverse activities and high traffic loads cause internet traffic congestion and frequent connection failures. The hotspot requires bandwidth management and access restrictions in order to efficient internet usage. Bandwidth management is carried out by the method Per Connection Queue (PCQ), and access restrictions are carried out with the firewall mangle. Mikrotik router OS configuration in practice manages bandwidth starting with connection marks and packet marks to separate connections to the router, through the router, and from the router to the internet. The parameter used to distinguish the traffic is the IP address which is grouped in dst-address and src-address to fulfill the pcq-classifier. Meanwhile, the blocking of access to streaming activities and online games is intended so the teachers only access related to education matters. To determine the success of the configuration, the Quality of service was calculated both before and after configuration. The results of the QoS throughput parameter which increased from 4.39% to 84.99%, the delay decreased from 462.52 ms to 146.87ms, and packet loss decreased from 27.94% to 0% on the network.